2017
DOI: 10.1002/adma.201700924
|View full text |Cite
|
Sign up to set email alerts
|

Tiered Electron Anions in Multiple Voids of LaScSi and Their Applications to Ammonia Synthesis

Abstract: Electrides-compounds in which electrons localized in interstitial spaces periodically serve as anions-have attracted broad attention for their exotic properties, such as extraordinary electron-donating ability. In our efforts to expand this small family of phases, LaScSi emerges as a promising candidate. Its electron count is 2e f.u. in excess of that expected from the Zintl concept, while its structure offers interstitial spaces that can accommodate these extra electrons. Herein, this potential is explored th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
123
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(144 citation statements)
references
References 40 publications
11
123
0
Order By: Relevance
“…NLO materials attract significant interest because of their wide applications in optical communication, optical computing, dynamic image processing, and other laser devices . Moreover, electrides are capable of boosting nitrogen dissociation, which, in turn, facilitates the process of ammonia synthesis . The first hyperpolarizability is the factor that determines the presence of NLO properties in materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NLO materials attract significant interest because of their wide applications in optical communication, optical computing, dynamic image processing, and other laser devices . Moreover, electrides are capable of boosting nitrogen dissociation, which, in turn, facilitates the process of ammonia synthesis . The first hyperpolarizability is the factor that determines the presence of NLO properties in materials.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13][14][15][16] Moreover, electrides are capable of boosting nitrogen dissociation, which, in turn, facilitates the process of ammonia synthesis. [6,[17][18][19][20][21] The first hyperpolarizability is the factor that determinest he presence of NLO properties in materials. As hyperpolarizabilities play decisive roles in the NLO properties, many experimental [22][23][24][25] and theoretical studies [26][27][28][29][30][31] of the first hyperpolarizability b of different materials were performed recently.T od ate, many attempts have been made to increase the hyperpolarizabilitieso fawide variety of organic molecules.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] Interestingly,s ome of these electridesc an boost nitrogen dissociation, facilitatingt he pro-cess of ammonia synthesis. [9][10][11][12][13][14] To date, fifteen(seven inorganic and eight organic)s olide lectrides have been reported, eight of which are stable at room temperature. [13,[15][16][17][18][19] In some other cases,t he electride character is revealed only at high pressure.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] To date, fifteen(seven inorganic and eight organic)s olide lectrides have been reported, eight of which are stable at room temperature. [13,[15][16][17][18][19] In some other cases,t he electride character is revealed only at high pressure. [20][21][22][23][24][25][26][27] Molecular electrides [28] are another type of electrides that have an electron( or as ignificant portion of an electron) that cannotb ea ssigned to any nucleus of the molecule, yet is relativelywell localisedin the molecular space.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that the ternary intermetallic compounds of the RTX family, where the R − rare‐earth, T, and X − different d ‐ and p ‐elements, respectively, have a wide variety of magnetic and electronic properties, presenting fundamental and practical interest, see recent reviews and other studies. A number of unusual physical phenomena observed in such compounds, for example, the giant magnetocaloric effect and magnetoresistance, are considered to be related with the peculiarities of hybridization of the localized 4 f ‐states of rare‐earth metals and conduction electrons in the electronic system.…”
Section: Introductionmentioning
confidence: 99%